Outcomes in Transplant Recipients Treated With Foscarnet for Ganciclovir-Resistant or Refractory Cytomegalovirus Infection. Issue 10 (October 2016) - Avery, Robin K.; Arav-Boger, Ravit; Marr, Kieren A.; Kraus, Edward; Shoham, Shmuel; Lees, Laura; Trollinger, Brandon; Shah, Pali; Ambinder, Rich; Neofytos, Dionysios; Ostrander, Darin; Forman, Michael; et al.
Abstract : Background: Antiviral-resistant or refractory cytomegalovirus (CMV) infection is challenging, and salvage therapies, foscarnet, and cidofovir, have significant toxicities. Several investigational anti-CMV agents are under development, but more information is needed on outcomes of current treatments to facilitate clinical trial design for new drugs. Methods: Records of solid organ transplant (SOT) and hematopoietic cell transplant (HCT) recipients at a single center over a 10-year period were reviewed retrospectively to characterize those who had received foscarnet treatment for ganciclovir-resistant or refractory CMV infection. Data were collected on virologic responses, mortality, and nephrotoxicity. Results: Of 39 patients (22 SOT, 17 HCT), 15 had documented ganciclovir resistance mutations and 11 (28%) of 39 had tissue-invasive CMV. Median duration of foscarnet was 32 days. Virologic failure occurred in 13 (33%) of 39 and relapses of viremia occurred in 31%. Mortality was 12 (31%) of 39 and was higher in HCT than SOT ( P = 0.001), although ganciclovir resistance was more common in SOT ( P = 0.003). Doses of ganciclovir or valganciclovir were low in 10 (26%) of 39 at some time before switching to foscarnet. Renal dysfunction occurred in 20 (51%) of 39 by end of treatment and in 7 (28%) of 25 after 6 months. Conclusions: Outcomes of existing treatment for ganciclovir-resistant or refractory CMV are suboptimal, in terms of virologic clearance, renal dysfunction, and mortality. These data should provide background information for future clinical trials of newer antiviral agents. Abstract : This report reviews the experience of a single, large transplant center in the United States and the outcomes of solid organ and hematopoietic stem cell transplant patients treated with foscarnet for refractory cytomegalovirus infection, concluding that outcomes are suboptimal.